Chronic pain through COVID - Dunham, M.; Bacon, L.; Cottom, S.; McCrone, P.; Mehrpouya, H.; Spyridonis, F.; Thompson, T.; Schofield, P. (Frontiers in Pain Research, 2022)
Objectives To identify good practice in the community management of chronic pain, and to understand the perspective of a group of healthcare service users towards the management of chronic pain using technology during the COVID-19 pandemic. Methods Forty-five people, recruited via social media and Pain Association Scotland, participated in three focus groups hosted over Zoom. Focus groups were conducted using semi-structured questions to guide the conversation. Data were analysed using Ritchie / Spencer's Framework Analysis. Results The participants shared observations of their experiences of remotely supported chronic pain services and insights into the potential for future chronic pain care provision. Experiences were in the majority positive with some describing their rapid engagement with technology during the COVID pandemic. Conclusion Results suggest there is strong potential for telehealth to complement and support existing provision of pain management services.